The twinning of Scottish general practices and Malawian clinics: the provision of email and internet services - Ron Neville; Sam Riddell; Pam Wilson; Paul Nkhoma (Journal of Innovation in Health Informatics, 2007)
Many patients and health care professionals in the developed world are uncomfortable about doing nothing in the face of the glaring inequities in health care between their own environment and that of Africa. In an effort to 'think global, act local' a Scottish GP practice used personal contacts to build a twinning link with a clinic serving a township in Malawi. This article describes the experience of establishing e-mail and internet services for Malawian health care staff to afford them the same level of access as developed world staff enjoy in accessing educational materials and professional supports. Using our twin link as an exemplar we are now matching other Scottish General Practices to Malawian Clinics around a common theme of modern communication media.